A Implementation of Clean Production in KS Tofu Factory (Kang Santri) in Kalipang Village, Rembang, Central Java (Penerapan Produksi Bersih Di Pabrik Tahu KS (Kang Santri) Di Desa Kalipang, Rembang, Jawa Tengah) - Nur Millah, Ika Ichya (Environmental Science Program, Ivet University, 2020)
Tofu is a food made from soybeans. The process of making tofu can produce solid and liquid waste which can cause environmental pollution. This study aims to determine the clean production and the process of making tofu through data collection by observation and direct interviews. The results showed that there were special dumpsites for tofu waste such as wells and their covers which were used for tofu waste water disposal. Tofu wastewater has high levels of Nitrogen (N), Phosphorus (P) and Potassium (K). Tofu wastewater also contains high protein so that the high nitrogen and phosphate content in wastewater can lead to unpleasant odors and eutrophication. For the tofu making process, there are several stages, namely soaking, milling, cooking, filtering and clumping which will then be sent to customers or sellers of tofu